Daniel Brown y David Fletcher. (2017). The effects of psychological and psychosocial interventions on sport performance: a meta-analysis. Sports medicine - González Insua, Francisco (2017)
Fil: González Insua, Francisco. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina